Effect of Rainfall on Digital/Analog Television Signals - Onaifo, Frank; Okandeji, Alexander Akpofure; Okubanjo, Ayodeji Akinsoji; Abdulsalam, Khadeejah; Alao, Peter (IPTEK The Journal for Technology and Science, 2025)
Rainfall has a strong negative impact on television (TV) signals, most especially at the receivers’ end. This is due to the propagation effect caused by atmospheric rain absorption of the wave signal. Television signals may reach the TV receiver unstable due to interferences caused by heavy rainfall, which creates undesirable poor-quality reception and noise. The effect of rain-induced attenuation on television signal reception is not enviable, especially when it is heavy. Consequently, this work aims to analyze the correlation between received signal strength and frequency of transmission during rainfall. The received signal strength measurements and rainfall data were collected concurrently during dry days and rainy days to achieve this aim. These readings were taken with a signal strength meter and other mobile phone software such as the rain gauge app, compass, etc.). Results show that rainfall leads to a noticeable degradation in the quality of received signals. Specifically, the data obtained were simulated, and it was observed that attenuations increase sharply as the rain rate increases. In particular, when the frequency is about 1080 GHz and the wavelength is low, there tends to be a disturbance between the drops of rainfall, which causes attenuation and results in low signal strength. To conclude, this work proposes a possible solution that is favorable to all television subscribers during rainfall.